Decreased retinal sensitivity in depressive disorder: a controlled study. (15th January 2018) - Berman, G.; Muttuvelu, D.; Berman, D.; Larsen, J. I.; Licht, R. W.; Ledolter, J.; Kardon, R. H.
Abstract : Objective: To compare pupil responses in depressed patients with a seasonal pattern, depressed patients without a seasonal pattern and healthy controls as a function of daylight hours on the testing day. Method: Patients suffering from a major depressive episode were included in wintertime. The pupil light reflex was measured at inclusion and in the following summer using a binocular pupillometer. A protocol of low (1 lux) and high (400 lux) intensity red and blue lights was used to assess rod, cone and melanopsin‐containing intrinsic photosensitive retinal ganglion cell input to the pupil reflex. Results: The mean group pupil responses associated with a melanopsin‐mediated sustained pupil response at 400 lux blue light were significantly reduced in the depressed subjects ( N  = 39) as compared to the healthy controls ( N  = 24) ( P  = 0.023). Across all groups, a reduction in number of daylight hours was significantly associated with a reduction in sustained pupil response ( P  = 0.007). All groups showed an equal effect of daylight hours on the melanopsin‐mediated sustained pupil response. Conclusion: The melanopsin‐mediated sustained pupil contraction to offset of high‐intensity blue light is reduced in depressed patients. These results further emphasize the interaction of light exposure with depression.